Vertical slum: the migratory movements and the Francoist housing policy - López Simón, Iñigo (Huarte de San Juan. Geografía e Historia, 2018)
During Franco’s dictatorship’s «Development» era, Spain experienced an unseen economical growth, that was called the spanish miracle, which main consecuences were the country’s industrial development, becaming the most important economical activity, that allowed for the consolidation of the middle class and the consume society. This economical growth was linked to migratory movements from rural areas to the industrial cities. In consecuence, several shanky towns and slumbs were built, which became in marginal neighbourhoods. A big and fast change happened, were a compulsive home building took place, consequently, serious social and economical differences appeared.